Developing a Measure of Spanish Phonological Awareness for Preschool Age Children: Spanish Individual Growth and Development Indicators. Issue 1 (2nd January 2019) - Wackerle-Hollman, Alisha; Durán, Lillian; Brunner, Stephanie; Palma, Jose; Kohlmeier, Theresa; Rodriguez, Michael C.
ABSTRACT: Spanish speakers in the United States are a steadily increasing population, up by 233% since 1980. Given the growing population of dual language learners (DLLs) and the large numbers of Spanish-speaking children enrolled in pre-kindergarten programs, addressing the educational needs of preschool-aged DLLs has become a national imperative. Specifically, the intersection of this growing population and the dearth of appropriate assessment tools to evaluate DLLs early language and literacy skills creates a need for assessments that accurately measure preschool performance. This manuscript reports on the iterative design process of a measure of Spanish phonological awareness for preschool-aged DLLs: Spanish Individual Growth and Development Indicators ( S-IGDI ) Primeros Sonidos. We employed measure design framework to develop the measure and tested item function within a study of 970, 4–5 year old DLLs. Results, including item level analyses and evidence regarding construct and criterion validity are reported.